Exercise technique manual for resistance training (Human Kinetics, 2008)
This book features a thorough checklists for 57 resistance training exercises, helping readers safely perform the exercises or oversee the safe and correct performance of them, instruction from experts who were selected and approved by the NSCA Certification Commission, over 140 photos that demonstrate proper execution of the exercises, and accurate exercise technique for each exercise on the DVDs, which also highlight some of the most common incorrect techniques